2005
DOI: 10.1007/s11664-005-0072-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of microstructure and V-defect formation in InxGa1−xN/GaN MQW grown using temperature-gradient metalorganic chemical vapor deposition

Abstract: Temperature-gradient metalorganic chemical vapor deposition (MOCVD) was used to deposit In x Ga 1-x N/GaN multiple quantum well (MQW) structures with a concentration gradient of indium across the wafer. These MQW structures were deposited on low defect density (2 ϫ 10 8 cm Ϫ2 ) GaN template layers for investigation of microstructural properties and V-defect (pinhole) formation. Room temperature (RT) photoluminescence (PL) and photomodulated transmission (PT) were used for optical characterization, which show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Atom probe tomography of 3 nm InGaN QWs showed that their upper interface was rougher than the lower one . Furthermore, studies on high indium content MQWs have demonstrated strain relaxation through introduction of line and extended defects [dislocations, stacking faults (SFs), V‐defects] that induce phase separation . However, in MQWs, it is difficult to separate the cumulative strain effect from the strain in isolated layers.…”
Section: Introductionmentioning
confidence: 99%
“…Atom probe tomography of 3 nm InGaN QWs showed that their upper interface was rougher than the lower one . Furthermore, studies on high indium content MQWs have demonstrated strain relaxation through introduction of line and extended defects [dislocations, stacking faults (SFs), V‐defects] that induce phase separation . However, in MQWs, it is difficult to separate the cumulative strain effect from the strain in isolated layers.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Line and extended defects, such as threading dislocations (TDs), can induce local indium clustering. [9][10][11][12][13] On the other hand, compositional pulling is a mesoscale phenomenon, whereby the compressive strain due to the interfacial misfit impedes incorporation of the larger indium atoms, causing a gradually increasing indium concentration with increasing film thickness. 14 Plasma-assisted molecular beam epitaxy (PAMBE), in principle, is a suitable growth method for achieving high (x > 0.2) indium contents.…”
mentioning
confidence: 99%
“…Hence, the information on overgrown v-shaped defects in pure GaN is limited. In transmission electron microscopy only v-shaped defects in multiple quantum wells formed by different group III-N alloys yield a strong contrast and were thus far investigated, 2,[6][7][8][9][10][11][12][13][14] focusing on the geometric structure of the v-shaped defects and the presence of further defects therein. However, in these cases the electronic structure may be modified by the presence of quantum wells.…”
mentioning
confidence: 99%